2009
DOI: 10.3174/ajnr.a1577
|View full text |Cite
|
Sign up to set email alerts
|

Volume-Based Morphometry of Brain MR Images in Adolescent Idiopathic Scoliosis and Healthy Control Subjects

Abstract: BACKGROUND AND PURPOSE: Adolescent idiopathic scoliosis (AIS) is a spinal deformity with unknown cause. Previous studies have suggested that subclinical neurologic abnormalities are associated with AIS. The objective of this prospective study was to characterize systematically neuroanatomic changes in patients with left thoracic AIS vs right thoracic AIS and healthy control subjects by using volumebased morphometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 32 publications
1
27
0
2
Order By: Relevance
“…36,37 Rousie et al . found correlations between basicranial labyrinthine measurements on MRI, labyrinth activity and lumbar scoliosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Rousie et al . found correlations between basicranial labyrinthine measurements on MRI, labyrinth activity and lumbar scoliosis.…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that subjects with AIS have 5% shorter distances between centers of the lateral and superior semicircular canals and 6% smaller posterior canals. 36,37 Using different morphological techniques, Zeng et al . found that vestibular canals are 9% longer and 2% thinner in people with AIS than controls.…”
Section: Resultsmentioning
confidence: 99%
“…3 Previous studies have reported changes in central nervous system structures in patients with AIS based on advanced medical imaging modalities. [4][5][6] Furthermore in a number of MR imaging studies, the observable changes in morphologic shape and position of the cord, 7 mismatch in lengthening between the cord and vertebral column, 8 and increased incidence of low-lying cerebellar tonsils 9 have led to the postulation of the presence of subclinical tethering of the spinal cord in AIS. 10 The proposed disturbed spinal cord function in AIS was further supported by the clinical observation of abnormal somatosensory function, which has been widely reported in this group.…”
mentioning
confidence: 99%
“…8 A study from Sweden provided further support on the higher incidence (3 times more common) of cerebellar tonsillar ectopia in scoliotic patients than controls, 2 and a study from our Nanjing AIS research group in China also confirmed a subgroup of AIS patients with tonsillar ectopia and abnormal SEP. 24 With recent advanced computational analysis technique, our group has also demonstrated abnormal changes in other structures within the central nervous system in AIS in a number of MRI-related studies. [25][26][27] These included morphologic changes in the brain and the spinal cord. The morphological changes in the cord, including altered shape and position of the cord at the scoliotic apex, shorter spinal cord length relative to the lengthened vertebral column, and increased incidence of low-lying cerebellar tonsils, lead to the hypothesis of spinal cord tethering in AIS.…”
Section: Discussionmentioning
confidence: 99%